2011
DOI: 10.1007/dcr.0b013e3182125577
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relationship Between Moderate Alcohol Intake and Rectal Cancer: Analysis of the North Carolina Colon Cancer Study

Abstract: Background The relationship between alcohol intake and rectal cancer is uncertain Objective We sought to evaluate whether alcohol consumption is associated with distal colorectal cancer and rectal cancer specifically. Design Data on alcohol intake were examined from the North Carolina Colon Cancer Study, a population-based case control study of distal colorectal cancer. Setting 33 counties in the central and eastern part of North Carolina Patients Cases had adenocarcinoma of the rectum, rectosigmoid, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 44 publications
2
32
0
4
Order By: Relevance
“…The reduced CRC risk associated with <30 g/d alcohol was found to be significant in only 2 studies: for nonobese individuals consuming between 13.5 and 27 g/d alcohol (Zhao et al, 2012), and for a Mediterranean population, where wine was a significant contributor to the alcoholic beverage type (Kontou et al, 2012). For all other studies, the risks associated with moderate alcohol consumption were not found to be statistically significant, but they consistently showed a reduced risk trend at moderate intake (Crockett et al, 2011;Nan et al, 2013;Park et al, 2010;Razzak et al, 2011).…”
Section: No Associated Crc Risk For Moderate Alcohol Intakementioning
confidence: 81%
See 4 more Smart Citations
“…The reduced CRC risk associated with <30 g/d alcohol was found to be significant in only 2 studies: for nonobese individuals consuming between 13.5 and 27 g/d alcohol (Zhao et al, 2012), and for a Mediterranean population, where wine was a significant contributor to the alcoholic beverage type (Kontou et al, 2012). For all other studies, the risks associated with moderate alcohol consumption were not found to be statistically significant, but they consistently showed a reduced risk trend at moderate intake (Crockett et al, 2011;Nan et al, 2013;Park et al, 2010;Razzak et al, 2011).…”
Section: No Associated Crc Risk For Moderate Alcohol Intakementioning
confidence: 81%
“…Wine consumption was also found to be independently associated with decreased CRC risk when consumed in moderation (Crockett et al, 2011;Kontou et al, 2012;Park et al, 2009), although 1 report found the benefit was significant only for men (Kontou et al, 2012). It is possible that too few women in the latter study consumed enough alcohol to receive the added benefit that men did, especially for wine consumption, where the polyphenolic content is hypothesized to provide antioxidant and anticarcinogenic effects (Kontou et al, 2012).…”
Section: No Associated Crc Risk For Moderate Alcohol Intakementioning
confidence: 84%
See 3 more Smart Citations